Interfacial engineering of RuO2 for electrocatalytic decomposition of Li2CO3 in Li–CO2/O2 battery - Zhang, Peng-Fang; Hu, Yi-Yang; Cui, Xin-Yu; Li, Jia-Hui; Zeng, Su-Yuan; Li, Jun; Hao, Hong-Guo; Kong, Xiang-Jin; Zhou, Yao; Li, Jun-Tao (Materials today physics, 2024)
Li2CO3, the primary byproduct of Li–CO2/O2 batteries, is challenging to decompose electrochemically and its accumulation cause the short lifespan of the battery. Herein, we report strong interfacial interaction between the intimately interfaced ultrafine RuO2 and Co3O4 nanoparticles, which leads to transfer of electrons from Ru 4d orbital to Co 3d orbital via interfacial Ru–O–Co bridges. Such intense interaction is found to boost the adsorption of CO2 and O2 on the RuO2; more importantly, it can also effectively decrease the energy barrier for the rate determining step of decomposition of Li2CO3. Therefore, both the formation and decomposition kinetics of Li2CO3 during charge and discharge are efficiently enhanced on the Co3O4-interfaced RuO2 compared to the freestanding RuO2. Using such Co3O4-interfaced RuO2 as cathode catalyst, Li–CO2/O2 (V:V = 4:1) batteries depict an overpotential as low as 1.31 V and a cycling stability of 137 cycles under a constant capacity of 1000 mAh g−1, which is significantly better than that with only Co3O4 or RuO2; the enhanced decomposition kinetics of Li2CO3 is also confirmed by monitoring the release of CO2 using in-situ mass spectrum. This work emphasizes the role of interfacial oxygen bridges in enhancing electrocatalytic decomposition of Li2CO3. [Display omitted] •Electrons transfer from Ru 4d to Co 3d orbital in the Co3O4–RuO2.•The Co3O4–RuO2 ensures Li–CO2/O2 battery with the best cycling performance.•The battery with the RuO2–Co3O4 cathode shows the largest evolution amount of CO2.•The reaction kenetics of Li2CO3 can be intensified with the Co3O4–RuO2 hybrids.